Authoritarianism and avarice lessons from a not too distant past [review of] - Palabrica, Jose T. (Philippine Journal of Public Administration, 1987)
A review of Alex Bello Brillantes, Jr., Dictatorship and Martial Law: Philippine Authoritarianism in 1972 (Manila: Great Books and UP College of Public Administration, 1987), 182 pages and Belinda A. Aquino, Politics of Plunder: The Philippines under Marcos (Manila: Great Books and UP College of Public Administration, 1987), 208 pages.